The Role of Social Media in Supporting University-Level Learning - Adhikari, Ram Prasad; Upadhyaya, Shankar Prasad; Adhikari, Bhashkar Chandra; Manjan, Arju; Rai, Kabina; Dulal, Manisha (International Research Journal of MMC, 2026)
The main aim of the study is to analyse the social media as an educational source. The study was carried out among the bachelor level students. The research study was guided by pragmatism philosophy and the cross-sectional survey research design was applied. Among the bachelor level students, 550 were selected from four faculty i.e. management, education, humanities and science by using simple random sampling method. SPSS version 27 was used to analyse data, and Independent-Samples Mann-Whitney U-Test and Independent-Samples Kruskal-Wallis Test were used to test hypotheses. Result showed that social medias were the basic study resources for University level students. They have used social media for listening to expert, searching for study materials, clearing the confusion, increasing learning interest, interacting with friends, learning cooperatively, establishing friendly relationship, and creating social connections. The null hypothesis "there is no significant difference between gender, caste and religion and their attitude towards social media as an educational resources" is rejected (p=0.000). The social medias were the crucial source of information, knowledge and skills for the university level students of this modern era.  They can search required information through various web portals of social media. The study provides insight to wise use of social media in education field, especially in university level for searching study materials as well as to create the collaborative learning environment. The universities and colleges should make policy and plan to integrate students' learning with social media and various web portals to make their students competent in this competitive world.